STRATEGI COPING PROBLEM-FOCUSED DALAM MENGATASI TINGKAT STRES PEGAWAI - Deli Arrahma; Ade Tiara Yulinda (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
The Problem-Focused Coping Strategy in Overcoming Employee Stress Levels in the Midst of Job Demands at the Seluma District Attorney's Office. This type of research uses qualitative descriptive with data collection techniques through observation, documentation, and interviews. Meanwhile, data analysis uses data reduction, data presentation, and conclusion drawn. The main findings of the study show that employees of the Seluma District Attorney's Office are indeed affected by work stress caused by various job demands ranging from high workloads, strict deadlines, lack of rest time, and large responsibilities that cause physical fatigue, emotional stress, and headaches. The problem-focused coping strategy that is often carried out by district attorney's employees usually starts from making work plans, grouping tasks according to priorities, arranging rest times, and seeking instrumental support from superiors or fellow colleagues who are more expert. Thus, overall, the results of the study show that  the problem-focused coping strategy  has been running effectively among employees of the Seluma District Attorney's Office in overcoming work stress stemming from job demands, and has been proven to help employees in controlling pressure, maintaining emotional balance, as well as maintaining the quality of performance at work. Keywords: Work Stress, Coping Problem-Focused